Improving the Competence of MGMP Informatics Teachers in Preparing Gamification-Based IBT in the Era of Education 5.0 - Ika Parma Dewi; Lativa Mursyida; Ari Suriani; Ryan Fikri; Randi Proska Sandra; Akrimullah Mubai; Rizkayeni Marta (Universitas Nurul Jadid, 2025)
The primary issue in technology-based learning assessment is the limited ability of teachers to utilize and develop gamification methods. Most teachers still rely on manual, paper-based evaluation techniques, resulting in suboptimal integration of technology in the assessment process. This challenge necessitates further exploration by education practitioners regarding the implementation of information technology (IT) in learning, particularly for MGMP Informatics teachers. This community engagement program, titled